Functional Traits of Pinus ponderosa Coarse Roots in Response to Slope Conditions - Dumroese, R. Kasten; Terzaghi, Mattia; Chiatante, Donato; Scippa, Gabriella S.; Lasserre, Bruno; Montagnoli, Antonio (Frontiers in Plant Science, 2019)
We excavated the root systems of Pinus ponderosa trees growing on a steeply sloped, volcanic ash-influenced soil in the northern Rocky Mountains of the United States to assess their functional coarse-root traits and root system architecture. Trees, outplanted as one-year-old seedlings from a container nursery, were in their 32nd growing season on the site. We found that the trees had deployed more roots, in terms of length and volume, in the downslope and windward quadrants than in their upslope and leeward quadrants, likely a response to mechanical forces toward improving stability. Moreover, we observed the development of three types of root cages (tight, enlarged, and diffused) that likely reflect micro-site characteristics. As the cage type transitioned from tight to enlarged to diffused we measured a decrease in the overall volume of the roots associated with the cage and the taproot becoming a more prominent contributor to the overall volume of the cage. Finally, we noted the development of specialty roots, namely those with I-beam and T-beam shapes in cross section, in the downslope quadrant; these types of roots are known to better counteract compression mechanical forces. These observations improve our understanding of root plasticity and tree rooting response to environmental stimuli, which is becoming an increasingly critical topic as changes in climate increase the frequency and intensity of storms.